La enfermedad subversiva: prácticas de guerra biológica en el conflicto armado colombiano y formas de cuidado afectivo en las FARC-EP (2021)
This research shows how the institutional management of leishmaniasis in Colombia is associated with biological warfare practices and forms of political violence from public health systems. It focuses on the analysis of the biopolitical management of Glucantime, the drug to treat this disease, and shows how leishmaniasis is intertwined with the dynamics of the armed conflict. Likewise, it explores the forms of community and affective care within the FARC-EP to resist and survive the war.